First comprehensive allergen-specific qPCR monitoring in European hake (Merluccius merluccius) muscle: Spatiotemporal distribution across seasons and Atlantic regions - C. Sousa; A. Filipa-Silva; R. Barracosa; A.R. Ribeiro; L.M.P. Valente; M.J. Santos; S. Gomes (Food Control, 2027)

Seaweed wrack alleviates copper toxicity in barley but fails to protect against combined copper and drought stress - Maria Martins; Clara Konrad; Bruno Sousa; Filipa Sousa; Pedro Mateus; José Moutinho-Pereira; Cristiano Soares; Fernanda Fidalgo (Algal Research, 2026)

First multi-contaminant assessment of the non-native American mink (Neogale vison) in Iberian freshwater ecosystems - Bárbara Lages; Ronaldo Sousa; Sara C. Cunha; Juliana Souza-Kasprzyk; José O. Fernandes; Alejandro Nieto Gámez; Miguel Fernandes Nóvoa; Américo Guedes; Pedro Alves; Przemyslaw Niedzielski; Paulo Cortez; Roberto Sargo; et al. (Journal of Hazardous Materials, 2026)

Fumonisins’ risk assessment in broa, a maize-based bread – An example from the Portuguese market - Pedro Nabais; Paulo Carmona; Sarogini Monteiro; Helena Sousa; Filipa Melo de Vasconcelos; Duarte Torres; Laura Cunha Silva (Food Control, 2026)

A contemporary systematic review on deterministic numerical simulations of light propagation in head tissues - Filipa Fernandes; Nuno Sousa; Filipe S. Silva; Óscar Carvalho; Susana O. Catarino (Biophysical Reviews, 2026)
Understanding how light interacts with the head’s tissues is relevant for several biomedical applications. Since in vivo studies involve ethical considerations, numerical simulations have become a recognised alternative method for studying light propagation in biological tissue. Although Monte Carlo methods are the gold standard for these studies, deterministic simulations are becoming more common due to their lower computational cost. Thus, this document reviews articles published after 2010, containing deterministic numerical simulations of light propagation (visible to infrared wavelengths) in human head tissues, to define how these methods are implemented and whether they are a viable alternative to the stochastic Monte Carlo algorithms. Most of the selected articles included a 3D simulation, using Finite Element Methods (FEM) to solve the Diffusion Equation (DE), with Robin boundary conditions, and considering the tissues as horizontal rectangular layers, to improve imaging techniques’ algorithms. Regarding target areas, there is an almost identical number of records studying the brain as a whole or dividing it into grey and white matter, while more studies consider the scalp and skull as individual layers instead of grouping them. The cerebrospinal fluid (CSF) was included in more than half of the studies, confirming that it is possible to simulate this tissue using the DE, if the optical parameters are adequate. Some of the challenges identified in the reported simulations are the variations in the optical properties of tissues (reduced scattering and absorption coefficients) and oversimplifications of the geometric models, which raise the question of whether using subject-specific data could improve the outcomes of light-based diagnosis and therapies. Although Monte Carlo methods are still the most commonly used for the simulation of optical properties, all the reviewed works reached comprehensive results, with most of them showing that deterministic numerical simulations can be an efficient and relatively accurate alternative to the time-consuming Monte Carlo methods.

Why marine gammarids belong to the future portfolio of aquafeed ingredients - Ricardo Calado; Marta Carvalho; Luísa Marques; Daniela P. Rodrigues; João P. Sousa; Felisa Rey; Maria Rosário Domingues; Joana Filipa Fernandes; Ruben X. G. Silva; Diana Madeira; Arne M. Malzahn; Óscar Monroig; et al. (Frontiers in Marine Science, 2025)
The sustainable supply of n-3 long-chain polyunsaturated fatty acids ( n -3 LC-PUFA) remains a major challenge for global aquaculture. Although plant oils, microalgae, genetically modified crops, insects, krill, and fish by-products have been explored as alternative sources, none currently provides a stand-alone solution for meeting the growing demand of n -3 LC-PUFA in aquafeeds’ production. Here, we present marine gammarids as a potential complementary source of these fatty acids. Our Perspective article focuses on the nutritional attributes of marine gammarids, including their naturally high levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and considers their biological traits that support aquaculture practicality. We also examine the potential of marine gammarids for circular bioeconomy applications through trophic upgrading of low-value side streams. While evidence from feeding trials is limited, preliminary data suggest marine gammarids may maintain their high EPA and DHA content even when fed on low-quality diets. Critical research priorities include developing scalable production systems, optimising feed formulations, evaluating performance across key aquaculture species, and assessing ecological and operational feasibility. This Perspective also highlights the potential of marine gammarids to contribute to a diversified and resilient aquafeed portfolio. Although they are unlikely to replace fish meal or fish oil entirely, marine gammarids may serve as a strategic complementary ingredient.

A Long-Term Overview of Elasmobranch Fisheries in an Oceanic Archipelago: A Case Study of the Madeira Archipelago - Mafalda Freitas; Filipa Pinho-Duarte; Madalena Gaspar; Pedro Ideia; João Delgado; Sara C. Cerqueira; Ricardo Sousa (Fishes, 2025)
Elasmobranch species are considered a global conservation priority due to their susceptibility to fishing pressure. In the Madeira Archipelago, Northeastern Atlantic, most elasmobranch species are caught as bycatch in artisanal drifting longline fishery targeting scabbardfishes. All commercial elasmobranch landings carried out in this archipelago over three decades (1990–2020) were analysed, aiming to provide a reliable overview of Madeira’s elasmobranch fisheries and their evolution. A total of 2316 tonnes of elasmobranchs were landed during the study period, corresponding to approximately EUR 2.1 million in first-sale value. The most representative period occurred from 2003 to 2013, corresponding to 75.21% of the total elasmobranch landings. A general pattern of supply and demand was evident, with mean price values typically showing an inverse trend to landed tonnage. At the species level, Centrophorus squamosus appears as the dominant species, representing about 89% of the total elasmobranch species landed, followed by Prionace glauca, with approximately 3%. The high dominance of C. squamosus in the scabbardfish fishery raises significant ecological and management concerns, as this deep-water shark species is known for its vulnerability to overexploitation. Management measures currently in place need to be updated and ought to be based on studies on the type and size of hooks for each fishery, to ultimately infer about species-specific survival rates, as well as the fishing gears’ soak time. Moreover, studies on the enhancement of food supply through fisheries discards are still missing, even though it is highly likely that this input may alter the dynamics of marine food webs.

Mapping marine debris hotspots on Boa Vista Island, Cabo Verde - Diana Sousa-Guedes; Neftalí Sillero; Mara Abu-Raya; Adolfo Marco; Filipa Bessa (Marine Pollution Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Characterisation of autophagy induction by the thiopurine drugs azathioprine, mercaptopurine and thioguanine in THP-1 macrophages - Connan D. Masson; Fern Findlay-Greene; Filipa Henderson Sousa; Paul Henderson; Jennifer A. Fraser; Peter G. Barlow; Craig Stevens (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Activating autophagy may be therapeutically beneficial, and we have previously shown that azathioprine (AZA), an immunomodulatory drug, induces autophagy. Here, we evaluated the induction of autophagy by the thiopurines AZA, mercaptopurine (6-MP) and thioguanine (6-TG) in THP-1 macrophages and investigated the mechanism of action in the context of this cellular process. The cytotoxicity of thiopurines was evaluated using an LDH assay. Induction of endogenous LC3 by thiopurines was evaluated using immunostaining. To confirm autophagy activation by thiopurines, a GFP-RFP-LC3 reporter plasmid was used to monitor the maturation of autophagosomes to autolysosomes. Induction of apoptosis by thiopurines was evaluated using Annexin V/PI staining, and ER stress was assessed via RT‒PCR analysis of XBP1 splicing. To gain insight into the mechanism of action of thiopurines, mTORC1 activity and eIF2α-S51 phosphorylation were evaluated by immunoblotting. Thiopurines were not cytotoxic to cells and induced strong time- and concentration-dependent autophagy. Thiopurines activate autophagy with complete progression through the pathway. Induction of autophagy by thiopurines occurred independently of apoptosis and ER stress. Immunoblotting revealed that AZA inhibited mTORC1 activity, and AZA and 6-TG increased eIF2α-S51 phosphorylation. In contrast, 6-MP had a minor effect on either signalling pathway. Thiopurines are strong inducers of autophagy, and autophagy induction should be considered among the mechanisms responsible for patient response to thiopurines.

How vulnerable are the nesting sites of loggerhead turtles in Cabo Verde? - Diana Sousa-Guedes; Adolfo Marco; Elton Neves; Maria Medina; Albert Taxonera; Kirsten Fairweather; Alberto Queiruga; Jairson Veiga; Juan Patino-Martinez; João Alírio; Filipa Bessa; Neftalí Sillero (Regional Environmental Change, 2025)
Marine turtles’ nesting grounds face imminent threats from urbanisation, climate change, and pollution. In this study, we estimated the vulnerability of loggerhead turtles ( Caretta caretta ) nesting beaches in Cabo Verde, one of the largest rookeries globally. We surveyed 61 sandy beach segments (~ 100 m) with a drone and modelled nest density by incorporating topographical and oceanographic variables. Then, we digitised all beaches across the islands, divided them into smaller sections (digitised segments), and projected the model onto this layer. Each digitised beach segment was evaluated considering their exposure to five risk factors: (a) marine litter density, (b) inundation trends, (c) land surface temperature trends, (d) light pollution trends, and (e) tourism pressure. Our analysis revealed that 48% of digitised segments are exposed to at least one threat. São Vicente, Santiago, and Sal are the most affected islands, mainly from marine debris and light pollution, while Santo Antão and Maio are the least impacted. Sal showed the highest overlap between vulnerable areas and high-density sites, highlighting its priority for conservation, though less affected islands should also be protected. We found that marine debris correlates positively with nest density, while light pollution negatively affects it. Our study emphasises the need for conservation efforts to ensure the sustainability of nesting sites amid escalating global changes.

Earthworm abundance increases aggregate stability: A field study in a Mediterranean agroforestry system - Filipa Reis; Eduardo Nascimento; Cristina Cruz; Teresa Dias; Katarina Hedlund; María J.I. Briones; Matty P. Berg; José Paulo Sousa; Pedro Martins da Silva (Applied Soil Ecology, 2025)

Yeast mycobiome of fruit and vegetable biowastes revealed by culture-dependent and metabarcoding approaches: Screening for the production of succinic acid and single cell oils - Filipa Gonçalves; Ticiana Fernandes; Joana Tulha; Daniela Bessa; Joana Pereira; Dorit Schuller; Maria João Sousa; Paula Sampaio; Célia Pais; Ricardo Franco-Duarte (Food Bioscience, 2024)

Enhancing tomato plants' tolerance to combined heat and salt stress – The role of arbuscular mycorrhizae and biochar - Bruno Sousa; Cristiano Soares; Filipa Sousa; Maria Martins; Pedro Mateus; Francisca Rodrigues; Manuel Azenha; José Moutinho-Pereira; Teresa Lino-Neto; Fernanda Fidalgo (Science of The Total Environment, 2024)

Evolution of heme biosynthesis in prokaryotes - Val Karavaeva; Filipa L. Sousa (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

No enzyme (or pathway) is an island: metals, prosthetic groups and coenzymes - Val Karavaeva; Sinje Neukirchen; Anastasiia Padalko; Jordi Zamarreno Beas; Filipa L. Sousa (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Monotopic quinone reductases from Staphylococcus aureus: The two alternative NADH: quinone oxidoreductases are players with different molecular and cellular roles - Filipa V. Sena; Filipe M. Sousa; Ana R. Pereira; Teresa Catarino; Eurico J. Cabrita; Mariana G. Pinho; Francisco R. Pinto; Manuela M. Pereira (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Efficacy of bacterial cellulose hydrogel in microfiber removal from contaminated waters: A sustainable approach to wastewater treatment - Filipa Rodrigues; Marisa Faria; Ivana Mendonça; Edward Sousa; Artur Ferreira; Nereida Cordeiro (Science of The Total Environment, 2024)

Beach wrack: Discussing ecological roles, risks, and sustainable bioenergy and agricultural applications - Maria Martins; Filipa Sousa; Cristiano Soares; Bruno Sousa; Ruth Pereira; Marcos Rubal; Fernanda Fidalgo (Journal of Environmental Management, 2024)

Assessment of the reproduction of six collembolan species in tropical soils naturally rich in potentially toxic elements - Gabriel Caixeta Martins; Filipa Alexandra de Ferreira Reis; Roberto Dall’Agnol; Sílvio Junio Ramos; Markus Gastauer; Tiago Natal-da-Luz; José Paulo Sousa; Luiz Roberto Guimarães Guilherme (Environmental Science and Pollution Research, 2024)

Lost and found: Patterns of marine litter accumulation on the remote Island of Santa Luzia, Cabo Verde - Diana Sousa-Guedes; Filipa Bessa; Alberto Queiruga; Leila Teixeira; Vitória Reis; José Alberto Gonçalves; Adolfo Marco; Neftalí Sillero (Environmental Pollution, 2024)

The role of connectivity in conservation planning for species with obligatory interactions: Prospects for future climate scenarios - Janine P. da Silva; Virgilio Hermoso; Manuel Lopes‐Lima; Rafael Miranda; Ana Filipa Filipe; Ronaldo Sousa (Global Change Biology, 2024)
Climate change may lead to range shifts, and barriers to such displacements may result in extirpations from previously suitable habitats. This may be particularly important in freshwater ecosystems that are highly fragmented by anthropogenic obstacles, such as dams and other smaller in‐stream barriers. Conservation planning in freshwaters should consider the dynamic effects of climate change and the ability of species to cope with it. In this study, we developed a framework for incorporating climate‐driven dispersal barriers into conservation planning taking into account the medium and long‐term impacts of climate change and species with obligatory interactions. Given that freshwater mussels (Bivalvia: Unionida) are a group of highly threatened organisms dependent on fish hosts to complete their larval development and dispersal, we used Marxan to prioritize areas for their joint conservation in the Iberian Peninsula as a case study. We tested two connectivity scenarios between current and future habitats, (i) unlimited dispersal capacity and (ii) dispersal constrained by artificial barriers, and also identified priority translocation areas for species that were unable to disperse. Accounting for the effects of climate change on species distributions allowed the identification of long‐term conservation areas, but disregarding artificial barriers to dispersal may lead to unrealistic solutions. Integrating the location of barriers allowed the identification of priority areas that are more likely to be colonized in the future following climatic shifts, although this resulted in an additional loss of six to eight features (~5%–7%) compared to solutions without dispersal constraints. Between 173 and 357 artificial barriers (~1.6%–3.3%) will potentially block species dispersal to irreplaceable planning units. Where removal of artificial barriers is unfeasible, conservation translocations may additionally cover up to eight additional features that do not meet conservation targets due to dispersal constraints. This study highlights the challenge of identifying protected areas to safeguard biodiversity under climate change.

Can plastic pollution contaminate loggerhead turtle nests? Evaluation of flame retardants (PBDEs) levels in the sand - Diana Sousa-Guedes; Sara C. Cunha; José O. Fernandes; Diana Semedo; Neftalí Sillero; Adolfo Marco; Filipa Bessa (Marine Pollution Bulletin, 2023)

Streams in the Mediterranean Region are not for mussels: Predicting extinctions and range contractions under future climate change - Janine P. da Silva; Ronaldo Sousa; Duarte Vasconcelos Gonçalves; Rafael Miranda; Joaquim Reis; Amílcar Teixeira; Simone Varandas; Manuel Lopes-Lima; Ana Filipa Filipe (Science of The Total Environment, 2023)

Joint species distribution models unveil co‐occurrences between freshwater mussels and their fish hosts - Janine P. da Silva; Duarte Vasconcelos Gonçalves; Aina Garcia‐Raventós; Manuel Lopes‐Lima; Simone Varandas; Elsa Froufe; Amílcar Teixeira; Francis K. C. Hui; Ana Filipa Filipe; Ronaldo Sousa (Journal of Biogeography, 2023)
Aim Freshwater mussels are among the most threatened taxa in the world, partially due to the dependence on fish hosts to complete their life cycle. Knowledge about the role of environmental and biotic drivers in determining mussels' distribution is currently lacking. We aimed to assess the role of environmental and biotic drivers in determining the distribution of mussels and their fish hosts and to test if co‐occurrence patterns were able to identify mussel‐host interactions. Location Douro River basin (Iberian Peninsula). Taxon Four freshwater mussels and ten fish hosts. Methods Joint species distribution models (JSDMs) were fitted to presence‐absence records for mussel and fish assemblages. Variance partitioning among environmental variables and latent variables was conducted to determine the environmental versus biotic drivers of species distributions. Resulting matrices of pairwise species co‐occurrences were used to identify co‐occurrence patterns. Results The distribution of host generalist mussel species was mainly explained by environmental variables related to climate and topography. The distribution of the host specialist Margaritifera margaritifera was mainly explained by land use. Strong positive correlations between mussels and the most relevant fish hosts were consistently captured by JSDMs. Co‐occurrence patterns were mainly explained by residual factors, indicating the potential role of biotic interactions. Main Conclusions Biotic interactions were expected to play an important role in explaining mussels' distribution, but the contribution of this factor was only meaningful for the host specialist M. margaritifera . Correlations between mussels and suitable hosts allowed to infer important fish hosts for freshwater mussels in the Douro River basin from distributional data alone. By finding similarities between the ecological requirements of co‐occurring species, conservation measures can be oriented towards several species, which brings a more holistic perspective to the protection of biodiversity.

Identifying freshwater priority areas for cross-taxa interactions - Joana Garrido Nogueira; Manuel Lopes-Lima; Pedro Beja; Ana Filipa Filipe; Elsa Froufe; Duarte V. Gonçalves; Janine P. da Silva; Ronaldo Sousa; Amílcar Teixeira; Simone Varandas; Virgilio Hermoso (Science of The Total Environment, 2023)

Modular structure of complex II: An evolutionary perspective - Val Karavaeva; Filipa L. Sousa (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Wrack Composed by Fucus spp, Ascophyllum nodosum and Pelvetia canaliculata Limits Metal Uptake and Restores the Redox Homeostasis of Barley Plants Grown in Cu-Contaminated Soils - Filipa Sousa; Maria Martins; Bruno Sousa; Cristiano Soares; Manuel Azenha; Ruth Pereira; Fernanda Fidalgo (Journal of Plant Growth Regulation, 2022)

Circulation and Transport Processes during an Extreme Freshwater Discharge Event at the Tagus Estuary - Ana Filipa Ribeiro; Magda Sousa; Ana Picado; Américo Soares Ribeiro; João Miguel Dias; Nuno Vaz (Journal of Marine Science and Engineering, 2022)
During the winter of 2013, the Tagus estuary was under the influence of intense winds and extreme freshwater discharge that changed its hydrodynamics and, consequently, the salt and heat transport. Moreover, the dynamics of the estuary may change due to climate change which will increase the frequency of heat waves and increase the mean sea level. Therefore, it is of utmost importance to study the impact of the future increase in air temperature and mean sea level under extreme events, such as that in the winter of 2013, to ascertain the foreseen changes in water properties transport within the estuary and near coastal zone. Several scenarios were developed and explored, using the Delft3D model suite, considering the results of the CMIP6 report as forcing conditions. Before the event, the mixing region of the estuary presented well-mixed conditions and its marine area a slight stratification. During the event, the estuary was filled with freshwater and the mixing region migrated toward the coast, leading to lower water temperature values inside the estuary. SLR has a higher impact on the salinity and stratification patterns than the air temperature increase. The response of water temperature is directly related to the increase in air temperature. The estuary mouth and the shallow regions will be more prone to changes than the upstream region of the estuary. The projected changes are directly linked to the future CO2 emissions scenarios, being intensive with the highest emission scenario.

Movements of Hatchery-Reared Dusky Groupers Released in a Northeast Atlantic Coastal Marine Protected Area - Ana Filipa Silva; Bárbara Horta e Costa; José Lino Costa; Esmeralda Pereira; João Pedro Marques; João J. Castro; Pedro G. Lino; Ana Candeias-Mendes; Pedro Pousão-Ferreira; Inês Sousa; Luís Bentes; Jorge M. S. Gonçalves; et al. (Journal of Marine Science and Engineering, 2022)
No-take areas are key instruments to promote the effectiveness of Marine Protected Areas (MPAs), particularly concerning the protection of endangered species such as the dusky grouper (Epinephelus marginatus). However, despite the establishment of no-take areas and the prohibition of catching this species in a southwestern Portuguese MPA (SACVMP—‘Sudoeste Alentejano’ and ‘Costa Vicentina’ Marine Park) since 2011, there is still no evidence of population recovery. By using acoustic biotelemetry, this work aimed to evaluate the feasibility of restocking hatchery-reared adult dusky groupers in two no-take areas within the SACVMP. In 2019 and 2021, thirty groupers were tagged with acoustic transmitters and the site attachment and movements of the groupers were assessed in the releasing sites (no-take areas). None of the tagged fish settled down in either of the areas, leaving the no-take areas mainly at dusk and night. Some individuals displayed extended movements of more than a hundred kilometers along the Portuguese coast which was rarely reported for this species. At least in some coastal stretches, those movements were performed close to the shore, which may evidence the importance of coastal MPAs to protect and promote the connectivity of species more associated with rocky reef habitats. Following studies should focus on the conditions that promote site attachment and fidelity by hatchery-reared dusky groupers so that future large-scale restocking programs can be successful in MPAs with appropriate habitats.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

The potential of beach wrack as plant biostimulant to mitigate metal toxicity: mineral composition, antioxidant properties and effects against Cu-induced stress - Filipa Sousa; Maria Martins; Bruno Sousa; Cristiano Soares; Manuel Azenha; Ruth Pereira; Fernanda Fidalgo (Journal of Applied Phycology, 2022)

Fifteen years of a nationwide culture collection of Neisseria gonorrhoeae antimicrobial resistance in Portugal - Miguel Pinto; João Carlos Rodrigues; Rui Matias; Ivone Água-Doce; Dora Cordeiro; Cristina Correia; João Paulo Gomes; Maria José Borrego; Filipa Alegria; Ana Jacinta Piedade; Maria Beatriz Tomaz; Cristina Toscano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Origin and history of Phoxinus (Cyprinidae) introductions in the Douro Basin (Iberian Peninsula): an update inferred from genetic data - Aina Garcia-Raventós; Filipa M. S. Martins; Amilcar Teixeira; Ronaldo Sousa; Elsa Froufe; Simone Varandas; Manuel Lopes-Lima; Pedro Beja; Ana Filipa Filipe (Biological Invasions, 2020)

Unravelling the antitumoral potential of novel bis(thiosemicarbazonato) Zn(II) complexes: structural and cellular studies - Elisa Palma; Hugo M. Botelho; Goreti Ribeiro Morais; Inês Rodrigues; Isabel Cordeiro Santos; Maria Paula Cabral Campello; Paula Raposinho; Ana Belchior; Susana Sousa Gomes; Maria Fátima Araújo; Isabel Correia; Nadia Ribeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2019)

Type II NADH:quinone oxidoreductase family: phylogenetic distribution, structural diversity and evolutionary divergences - Bruno C. Marreiros; Filipa V. Sena; Filipe M. Sousa; Ana P. Batista; Manuela M. Pereira (Environmental Microbiology, 2016)
Summary Type II NADH:quinone oxidoreductases (NDH‐2s) are membrane proteins, crucial for the catabolic metabolism, because they contribute to the maintenance of the NADH/NAD + balance. In several pathogenic bacteria and protists, NDH‐2s are the only enzymes performing respiratory NADH:quinone oxidoreductase activity. For this reason and for being considered absent in mammals, NDH‐2s were proposed as suitable targets for novel antimicrobial therapies. We selected all sequences of genes encoding NDH‐2s from fully sequenced genomes present in the KEGG database. These genes were present in 61% of the 1805 species belonging to Eukarya (83%), Bacteria (60%) and Archaea (32%). Notably sequences from mammal species including humans were retrieved in our selection as NDH‐2s. The data obtained and the already available information allowed systematizing several properties of NDH‐2s: (i) the existence of additional sequence motifs with putative regulatory functions, (ii) specificity towards NADH or NADPH and (iii) the type of quinone binding motif. We observed that NDH‐2 family distribution is not congruent with the taxonomic tree, suggesting different origins for the eukaryotic sequences and possible lateral gene transfer among prokaryotes. We note the absence of genes coding for NDH‐2 in anaerobic phyla and the presence of multiple copies in several genomes, specifically in cyanobacteria. These observations inspired us to propose a metabolic hypothesis for the appearance of NDH‐2s.

Axonal elongation and dendritic branching is enhanced by adenosine A2A receptors activation in cerebral cortical neurons - Filipa F. Ribeiro; Raquel Neves-Tomé; Natália Assaife-Lopes; Telma E. Santos; Rui F. M. Silva; Dora Brites; Joaquim A. Ribeiro; Mónica M. Sousa; Ana M. Sebastião (Brain Structure and Function, 2016)

Labellum transcriptome reveals alkene biosynthetic genes involved in orchid sexual deception and pollination-induced senescence - Filipa Monteiro; Mónica Sebastiana; Andreia Figueiredo; Lisete Sousa; Helena C. Cotrim; Maria Salomé Pais (Functional & Integrative Genomics, 2012)

Cultivar-specific kinetics of gene induction during downy mildew early infection in grapevine - Andreia Figueiredo; Filipa Monteiro; Ana Margarida Fortes; Martina Bonow-Rex; Eva Zyprian; Lisete Sousa; Maria Salomé Pais (Functional & Integrative Genomics, 2012)

Isolation and characterization of novel polymorphic nuclear microsatellite markers from Ophrys fusca (Orchidaceae) and cross-species amplification - Helena C. Cotrim; Filipa A. Monteiro; Eva S. Sousa; Michael F. Fay; Mark W. Chase; Maria S. Pais (Conservation Genetics, 2009)

Genetic structure and signature of population decrease in the critically endangered freshwater cyprinid Chondrostoma lusitanicum - Vítor Sousa; Filipa Penha; Maria J. Collares-Pereira; Lounès Chikhi; Maria M. Coelho (Conservation Genetics, 2008)